A phenomenological study on the experiences of nursing home nurses - Nilay Ercan-Şahin; Mücahide Öner (BMC Nursing)
Abstract Background The nursing home is a multifaceted environment where residents, many of whom have multiple chronic conditions, typically spend their final years receiving care. Being a nurse in a nursing home is a challenging and multifaceted role that demands a range of skills. The study aimed to explore the experiences of nursing home nurses, with the aim of gaining a deeper understanding of what it means to be a nurse in a nursing home, both professionally and personally. Methods Seventeen nurses working in nursing homes in Ankara, Turkey were recruited between June and Agust 2024 for a descriptive phenomenological study. Data were collected through in-depth face-to-face interviews and analyzed using thematic analysis. The study was reported according to the Consolidated Criteria for Reporting Qualitative Research Checklist. Findings Six themes emerged from descriptive analysis “Transformation”, “Wish to Die Before Experiencing Aging”, “Needs and Shortcomings in Older Adults Care”, “Communication Challenges”, “Struggles with Professional Fulfillment”, “Perspectives on Aging in Residential Care”. Conclusions This study demonstrates that working with older adults in nursing homes can be highly stressful for nurses, potentially leading to negative effects on their professional and personal experiences.